Kinematic, arm-stroke efficiency, coordination, and energetic parameters of the 400-m front-crawl test: A meta-analysis - Correia, Ricardo de Assis; Feitosa, Wellington Gomes; Castro, Flávio Antônio de Souza (Frontiers in Sports and Active Living, 2023)
Several studies have investigated biomechanical and energetic parameters in competitive swimming. Among these studies, it is possible to identify the 400-m front crawl as a useful test to assess these parameters. The present study provided a meta-analysis assessing representative variables for the kinematic, arm-stroke efficiency, coordination, and energetic parameters of the 400-m front crawl test. PubMed, Embase, Web of Science, and SPORTDiscus were the databases used to select the studies published between January 1970 and December 2022. Forty studies (n = 651 swimmers) were selected according to the eligibility and inclusion criteria. The variables chosen to represent each parameter were: clean swim speed (kinematics); index of coordination (coordination); arm-stroke efficiency (efficiency); and oxygen consumption (energetic). Swimming speed was moderate (1.34 m·s-1) compared to the world's records performers. Thus, this speed contributed for the swimmers in remaining at high efficiency (35%), imposing a capture coordination model (index of coordination: -11%) with high oxygen consumption (58.8 ml·kg-1·min-1). High heterogeneity (>75%) was found among the outcome parameters in the studies. The different average speeds that represented the kinematic parameters seem to be the most responsible and influential in the arm-stroke efficiency, coordination, and energetic parameters for high 400-m freestyle (front crawl) performance. This meta-analysis can help researchers, coaches, and swimmers improving competitive performance, and developing further research in the sports sciences area, specifically in the swimming.